Oil Price Fluctuations and Their Impact on Macroeconomic Variables: The Case of South Africa - Ngobeni, Mkateko; Dagume, Mbulaheni Albert (International Journal of Energy Economics and Policy, 2026)
Oil price volatility has a significant impact on macroeconomic performance, presenting challenges for policymakers in both oil-exporting and oil-importing countries. This study examines the impact of oil price fluctuations on economic growth, inflation, and unemployment in South Africa over the period January 2000 to December 2021, capturing more than two decades of economic and oil market dynamics, including major shocks such as the 2008 global financial crisis, the 2014 oil price collapse, and the COVID-19 pandemic. We explore short- and long-term relationships among these variables using the Johansen cointegration approach and a Vector Error Correction Model (VECM). Unit root tests indicate all series, except inflation, are stationary in first differences, and Granger causality tests reveal non-statistically significant short-run causality. Variance decomposition shows crude oil prices, inflation, and GDP account for a substantial share of unemployment variation over time. The analysis reveals a negative long-term relationship between oil prices and key macroeconomic indicators, suggesting that rising oil prices have an adverse impact on South Africa’s economy. Diagnostic tests confirm model adequacy, with no evidence of heteroscedasticity and normally distributed residuals. These findings underscore the importance of incorporating oil price volatility into macroeconomic planning and the need for continued research on these dynamic relationships.